Proceedings of the 11th International Workshop on Semantic Evaluation (SemEval-2017) 2017
DOI: 10.18653/v1/s17-2170
|View full text |Cite
|
Sign up to set email alerts
|

WING-NUS at SemEval-2017 Task 10: Keyphrase Extraction and Classification as Joint Sequence Labeling

Abstract: We describe an end-to-end pipeline processing approach for SemEval 2017's Task 10 to extract keyphrases and their relations from scientific publications. We jointly identify and classify keyphrases by modeling the subtasks as sequential labeling. Our system utilizes standard, surface-level features along with the adjacent word features, and performs conditional decoding on whole text to extract keyphrases.We focus only on the identification and typing of keyphrases (Subtasks A and B, together referred as extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Teams Overall A B C s2 end2end (Ammar et al, 2017) 0.43 0.55 0.44 0.28 TIAL UW 0.42 0.56 0.44 TTI COIN (Tsujimura et al, 2017) 0.38 0.5 0.39 0.21 PKU ICL (Wang and Li, 2017) 0.37 0.51 0.38 0.19 NTNU-1 0.33 0.47 0.34 0.2 WING-NUS (Prasad and Kan, 2017) 0.27 0.46 0.33 0.04 Know-Center (Kern et al, 2017) 0.27 0.39 0.28 SZTE-NLP (Berend, 2017) 0.26 0.35 0.28 NTNU (Lee et al, 2017b) 0.23 0.3 0.24 0.08 LABDA (Flores et al, 2017) 0.04 0.08 0.04 upper bound 0.84 0.85 0.85 0.77 random 0.00 0.03 0.01 0.00 former is surprising, as keyphrases are with an overwhelming majority noun phrases, the latter not as much, many keyphrases only appear once in the dataset (see Table 1). GMBUAP further tried using empirical rules obtained by observing the training data for Subtask A, and a Naive Bayes classifier trained on provided training data for Subtask B.…”
Section: Competitions/15898mentioning
confidence: 99%
“…Teams Overall A B C s2 end2end (Ammar et al, 2017) 0.43 0.55 0.44 0.28 TIAL UW 0.42 0.56 0.44 TTI COIN (Tsujimura et al, 2017) 0.38 0.5 0.39 0.21 PKU ICL (Wang and Li, 2017) 0.37 0.51 0.38 0.19 NTNU-1 0.33 0.47 0.34 0.2 WING-NUS (Prasad and Kan, 2017) 0.27 0.46 0.33 0.04 Know-Center (Kern et al, 2017) 0.27 0.39 0.28 SZTE-NLP (Berend, 2017) 0.26 0.35 0.28 NTNU (Lee et al, 2017b) 0.23 0.3 0.24 0.08 LABDA (Flores et al, 2017) 0.04 0.08 0.04 upper bound 0.84 0.85 0.85 0.77 random 0.00 0.03 0.01 0.00 former is surprising, as keyphrases are with an overwhelming majority noun phrases, the latter not as much, many keyphrases only appear once in the dataset (see Table 1). GMBUAP further tried using empirical rules obtained by observing the training data for Subtask A, and a Naive Bayes classifier trained on provided training data for Subtask B.…”
Section: Competitions/15898mentioning
confidence: 99%
“…The task asked to extract such entities and identify the relations among them on short excerpts of scientific documents. State-of-the-art deep learning and feature-based sequential labeling models set the standard for approaches on such tasks, using Long Short-Term Memory (LSTM) (Ammar et al, 2017) and Conditional Random Field (CRF) (Prasad and Kan, 2017) models, respectively.…”
Section: Related Workmentioning
confidence: 99%
“…(Akhundov et al, 2018) have shown how BiLSTM-CRF can be used for this task. (Prasad and Kan, 2017) shows the extraction of keyphrases and relation prediction using CRFs for sequence labeling.…”
Section: Related Workmentioning
confidence: 99%